GE_GERICHTE P/24664/2022 vom 6. Februar 2023 - GE Cour de justice (2023)
PERSONNE PROCHE;HÉRITIER;HOMICIDE PAR NÉGLIGENCE;MÉDECIN;SUICIDE;BESOIN DE SURVEILLANCE;DEVOIR PROFESSIONNEL | CPP.116.al2; CEDH.3; CEDH.2; CP.117; CPP.121; CPP.122; CPP.382.al3; LEPM.5.al1; LREC.2; LREC.9; CPP.136; CPP.383